2015
DOI: 10.1007/s12011-015-0556-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bone Tissue Elements Between Normal and Osteoarthritic Pelvic Bones in Dogs

Abstract: Physiochemical analysis of bones affected with osteoarthritis (OA) can be used to better understand the etiology of this disease. We investigated the percentage of chemical elements in canine pelvic bone affected with varying degrees of OA using a handheld X-ray fluorescence (XRF) analyzer that discriminates magnesium (Mg(12)) through bismuth (Bi(83)). A total of 45 pelvic bones, including both ilium and subchondral acetabular bone plates, were categorized as normal (n = 20), mild grade OA (n = 5), moderate gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Speculatively, the elemental composition may be not be homogenous in cross-sectional areas of the horn, leading to varied elemental content between layers of keratinized tissue. Indeed, our previous work has shown that elemental distributions can vary across longitudinal and transversal sites of various tooth and bone types [ 3 , 12 , 13 ]. Finally, the difference in results may be related to the specific elements measured in each study.…”
Section: Discussionmentioning
confidence: 99%
“…Speculatively, the elemental composition may be not be homogenous in cross-sectional areas of the horn, leading to varied elemental content between layers of keratinized tissue. Indeed, our previous work has shown that elemental distributions can vary across longitudinal and transversal sites of various tooth and bone types [ 3 , 12 , 13 ]. Finally, the difference in results may be related to the specific elements measured in each study.…”
Section: Discussionmentioning
confidence: 99%
“…This study analyzed 45 os coxae bones and these were categorized as normal, mild grade OA, moderate grade OA, and severe grade OA. The findings of this study suggest that these two elements may be useful in future studies on the etiology and pathophysiology of OA (Nganvongpanit et al 2016b).…”
Section: Elemental Studymentioning
confidence: 84%
“…Moreover, the observations of Nganvongpanit et al showed a higher iron concentration in the synovial fluid in the degenerated knee joints. The decrease in the iron concentration, along with the advancement of the degenerative changes, may be one of the reasons for the loss of flexibility in the intervertebral disc, due to the reduction in the biosynthesis of collagen fibers and elastin, for which the iron ions are necessary [ 41 ].…”
Section: Discussionmentioning
confidence: 99%